Mortality and patient disposition after ICU tracheostomy for secretion management vs. prolonged ventilation: a retrospective cohort study - Dominique Dundaru-Bandi; Linda M. Zhu; Milana Schipper; Paul J. Warshawsky; Blair C. Schwartz (BMC Anesthesiology)
Abstract Background There is little research on long-term, patient-centered outcomes in critically ill patients undergoing tracheostomy for secretion management or prolonged ventilation. The goal of this study was to determine and compare hospital and long-term mortality, and incidence of new institutionalization amongst patients who underwent an ICU tracheostomy for these two aforementioned indications. Methods This was a single center historic cohort study of all ICU patients who received a tracheostomy for secretion management or prolonged ventilation from 2011 to 2022. We compared hospital and long-term mortality and incidence of new institutionalization between these two groups. Results A cohort of 247 patients (133 secretion management, 114 prolonged ventilation) was established. Overall hospital mortality was 86/247 (35%), mortality at 1 year was 106/207 (51%), and at 3 years was 117/167 (70%), with no significant difference between the two indications. Patients with prolonged ventilation indication had a significantly higher ICU mortality [34/114 (30%) vs. 13/133 (10%), P < 0.001]. Amongst hospital survivors, 49/137 (36%) were unable to return home, with significantly more patients tracheostomized for secretion management requiring new institutionalization [37/78 (47%) vs. 12/59 (20%), P = 0.002]. Conclusions Tracheostomy indication may be an important determinant of short- and long-term patient-centered outcomes. Patients receiving a tracheostomy for secretion management were twice as likely to be discharged to a new institution compared to prolonged ventilation patients. Patient-centered outcomes should be included in future studies and if confirmed, these outcomes should be incorporated into discussions about tracheostomy decision making.